Desarrollo e implementación de un software educativo para la asignatura de estudios sociales “el mundo en el que vivimos” como herramienta de apoyo para el proceso de enseñanza - aprendizaje del cuarto año de educación básica del centro educativo comunitario intercultural bilingue “Yaguarzongo” del cantón Saraguro, provincia de Loja. Período lectivo 2013 - 2014 - Macas Puchaicela, Gladys Maria (2014)
This thesis was conducted in the Canton province of Loja Saraguro. and focuses on it, DEVELOPMENT AND IMPLEMENTATION OF AN EDUCATIONAL SOFTWARE FOR THE SOCIAL STUDIES SUBJECT " THE WORLD WE LIVE” AS A TOOL TO SUPPORT THE BASIC EDUCATION FOURTH YEAR TEACHING - LEARNING PROCESS OF "YAGUARZONGO" BILINGUAL INTERCULTURAL COMMUNITY EDUCATIONAL CENTER SARAGURO CANTON, PROVINCE. LOJA PERIOD 2013 - 2014. The general objective was to Develop and implement an educational software in the Subject: Social Studies, The World in Which We Live, and Tool Support for Teaching Process - Learning the Fourth Year Basic Education Center Intercultural Bilingual community "Yaguarzongo" Saraguro Canton, Loja Province teaching period 2013 -. 2014. The methods used for the development of the thesis project were: Scientific Method, deductive, inductive, synthetic Analytical statistical model allowing also the orientation of each of the development phases of the investigation. Techniques were also used as the survey, interview, observation and record validation for students and teachers of the subject of Social Studies of the Fourth Year of Intercultural Bilingual Education Center "Yaguarzongo" technical resources that were used to prepare the Educational Software was the flash CS5 tools. The results obtained when surveying students were 57% students said that their teacher used the book for their classes, and 100% say they would be willing to use the educational software in the Course of Studies social, with 50% saying that the resources they would like to have the Software are the videos because this way learn faster. Finally, this educational software in its presentation in question number three says teacher with 100% interest they aroused the students, 86% of them used any aid rest in the Software, and the grade received this technological tool was 100% calling it good; Educational Software serving as a teaching tool to enhance the learning experience for students in the fourth year of Intercultural Bilingual Education Center "Yaguarzongo".